The Use of Total Reflection X-Ray Fluorescence in an Underwater Archaeology Case Study - Vázquez, Cristina; Boeykens, Susana Patricia; Elkin, Dolores Carolina (Society for Historical Archaeology, 2010)
Fil: Vázquez, Cristina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina